The outsider - Camus, Albert, 1913-1960.; Laredo, Joseph; Penguin Books (London : Penguin Books, 2000)
French author Albert Camus's 1942 novel, "The Stranger," in which a quiet clerk in Algiers commits a murder, caught in the grip of forces he does not understand.
Based on the original French text.
Young Adult
Keywords: Murder -- Fiction; Adventure fiction; Bilingual books -- English-Korean.; Homicide -- Fiction; Algeria -- Fiction